Cytoplasmic iron deposition is associated with the expression of oxidative DNA damage marker in meningiomas. Issue 5 (13th February 2013) - Nagaishi, Masaya; Yokoo, Hideaki; Osawa, Tadashi; Nobusawa, Sumihito; Tanaka, Yuko; Ikota, Hayato; Yoshimoto, Yuhei; Nakazato, Yoichi
<x xml:space="preserve">Abstract</x> Angiomatous meningiomas are rare meningioma subtypes, which are characterized by abundant, well‐formed vessels. We encountered two cases of newly diagnosed angiomatous meningiomas exhibiting tumor cells with brown pigments, which were histochemically proven to be iron. In an attempt to understand its pathological significance, we assessed this unusual finding in representatives for each grade of meningiomas and immunoexpression of transferrin receptor (CD71) and the oxidative DNA damage marker, 8‐hydroxy‐2′‐deoxyguanosine (8‐OHdG). Iron deposition in the tumor cells was observed in 8/15 (53%) angiomatous meningioma cases, 2/6 (33%) microcystic meningiomas and 2/20 (10%) meningothelial meningiomas, which included clustered microvessels, but not in fibrous, atypical or anaplastic meningiomas (P = 0.001). Cytoplasmic CD71 expression was largely negative in angiomatous meningioma cases, but positive in meningothelial and high‐grade meningiomas, suggesting that the transferrin‐dependent iron transporter was involved in iron uptake in meningiomas. Nuclear expression of 8‐OHdG was observed in ≥50% of the tumor cells in all 15 cases of angiomatous meningioma and was associated with the presence of regressive histopathological findings, such as hyalinized vessels and cystic changes. In addition, the fraction of iron‐containing tumor cells was correlated to those expressing 8‐OHdG (P = 0.005). Our finding indicates that cytoplasmic iron deposition in tumor cells is characteristic of highly vascularized benign meningiomas and related to increased oxidative DNA damage markers.